CyanoStat: An open-source platform for CO2 regulation in microbial incubators optimized for cyanobacterial cultivation - Tijn O. Delzenne; Dennis Claessen (HardwareX)
Accurate and reliable control of CO2 is essential for the incubation of many microbial organisms. Photosynthetic microbial organisms, such as cyanobacteria, pose a particular challenge, requiring both light and elevated CO2 concentrations for efficient growth. These characteristics highly limit the availability of affordable and reliable incubation devices, deterring laboratories from undergoing proof-of-concept research into cyanobacteria. To combat this, this study presents CyanoStat: an affordable add-on device for off-the-shelf microbial incubators. By consistently measuring the CO2 concentrations in an incubator, control is achieved by opening and closing the flow of gas from a pressurized bottle to the incubator. Through a tuned time-based valve control system, the device is able to rival the accuracy and stability of significantly more expensive hardware. Multiple implemented safety features allow for reliable usage over prolonged periods. CyanoStat, as described in this work, was able to achieve precise CO2 control with fluctuations of 120 ppm, 145 ppm and 260 ppm around a setpoint of 1, 2 and 5%, respectively. This demonstrates that the system is well-suited for both short-term proof-of-concept studies and long-term cultivation applications.